2019
DOI: 10.3390/brainsci9120366
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Biomarkers are Correlated with Some Forms of Regressive Autism Spectrum Disorder

Abstract: Background: Several studies have tried to investigate the role of inflammatory biomarkers in Autism Spectrum Disorder (ASD), and their correlations with clinical phenotypes. Despite the growing research in this topic, existing data are mostly contradictory. Methods: Eighty-five ASD preschoolers were assessed for developmental level, adaptive functioning, gastrointestinal (GI), socio-communicative and psychopathological symptoms. Plasma levels of leptin, resistin, plasminogen activator inhibitor-1 (PAI-1), macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 73 publications
0
11
1
Order By: Relevance
“…In fact, in the current study, the supplementation with DSF compared with placebo resulted in no significant effects on the levels of plasma and fecal inflammatory biomarkers. In a previous investigation, we have reported that the values of these biomarkers were in the normal range already at baseline ( 51 ); thus, we do not confirm the two previous studies ( 52 , 53 ) reporting some positive effects of probiotics on biomarkers of inflammation, and we could hypothesize that the effect of probiotics on adaptative functioning is not mediated by a reduction in systemic or intestinal inflammation.…”
Section: Discussioncontrasting
confidence: 90%
“…In fact, in the current study, the supplementation with DSF compared with placebo resulted in no significant effects on the levels of plasma and fecal inflammatory biomarkers. In a previous investigation, we have reported that the values of these biomarkers were in the normal range already at baseline ( 51 ); thus, we do not confirm the two previous studies ( 52 , 53 ) reporting some positive effects of probiotics on biomarkers of inflammation, and we could hypothesize that the effect of probiotics on adaptative functioning is not mediated by a reduction in systemic or intestinal inflammation.…”
Section: Discussioncontrasting
confidence: 90%
“…Our finding of increased DNAmPAI-1 in individuals with ASD may support this hypothesis. Moreover, plasma PAI-1 levels were significantly higher in individuals with ASD and both regression and a developmental delay compared to individuals with ASD without regression, or individuals with ASD and regression without a developmental delay [ 43 ]. In contrast, no association was observed between ASD and the 4G/5G sequence polymorphism in the PAI-1 gene promoter that influences the level of plasma PAI-1 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are great controversies regarding the role of pro-inflammatory cytokines in ASD. Despite the presence of a specific plasmatic cytokine profile in children with regressive ASD, recently, Prosperi et al [ 67 ] did not support the use of cytokines as markers of leaky gut and did not support anti-inflammatory therapies in ASD-affected children. They recommended the search of alternative hypotheses for the etiology of GI symptoms in ASD-affected individuals.…”
Section: Biomarkers Of Leaky Gut In Asdmentioning
confidence: 99%